De um projeto de desenvolvimento nacional à subordinação ao capital externo: a dinâmica da indústria brasileira de máquinas agrícolas - Flores , Edson Luiz (2021)
This research, in which we study the dynamics of the Brazilian agricultural machinery industry, led us to defend the following thesis: in Brazil, this industrial segment had a late development compared to that of other countries, such as the United States, Germany and England. It turns out that the Brazilian social formation, crystallized from the Portuguese occupation, developed an agro-export economy, in general, supported by manual labor contributed to delay the insertion of machinery in agriculture. The classes that controlled the country's economy before the 1930s (farmers and the export/import trade), practically did not support industrialization, which delayed technological development, for example, with little development in the steel industry and the mechanical sector, essential for the manufacture of agricultural machinery. However, from that period (with the change in the power pact) the basic industry (iron, steel, oil, energy, among others) and the automotive sector began to emerge in Brazil, which stimulated the agricultural machinery manufacturing segment, so that since the 1960s, even tractors (especially by branches of foreign companies), self-propelled harvesters (with a predominance of national companies) and the most diverse agricultural implements have been produced, resulting in the 1970s practically consolidating this industrial sector, with several companies concentrated especially in the states of São Paulo and Rio Grande do Sul. This process was stimulated through economic policies to support the industry, like the National Plan for the Wheel Tractor Industry (1959), National Development Plans (PND’s), in addition to encouraging the formation of demand for the sale of agricultural machinery, particularly through rural investments credit. However, the economic policies implemented since the 1980s did not supported the industrialization and reduced rural credit, which resulted in a process of underutilization of the productive capacity of the agricultural machinery industry installed in Brazil, widening the recession and causing, particularly the As of the 1990s, the bankruptcy of important national companies, as well as facilitating the entry of foreign capital, which acquired other outstanding industrial units in this segment. Even with the resumption of rural credit, which occurred particularly in the period 2006-2013, which rekindled domestic sales in the agricultural machinery industry, the denationalization of companies persisted, so that at present this sector is oligopolized, controlled by few brands concentrated in three major foreign industrial groups: AGCO Corporation, CNH Industrial and Deere & Company. Apparently, they are dominant industrial groups, but which are fundamentally controlled by financial capital, by few investment funds (based mainly in the United States and Europe) which share practically the entire world, including, controlling industrial corporations in other segments.